Serial assessment of suspected myelodysplastic syndromes: significance of flow cytometric findings validated by cytomorphology, cytogenetics, and molecular genetics - Wolfgang Kern; Claudia Haferlach; Susanne Schnittger; Tamara Alpermann; Torsten Haferlach (Haematologica, 2013)
The significance of flow cytometry indicating myelodysplasia without proof of myelodysplasia by cytomorphology remains to be clarified. We evaluated follow-up analyses in 142 patients analyzed in parallel by flow cytometry, cytomorphology and cytogenetics for suspected myelodysplasia without proof of myelodysplasia by cytomorphology. At initial assessment, flow cytometry indicated myelodysplasia in 64 of 142 (45.1%) patients. In 9 of 142 (6.3%) patients, cytogenetics revealed aberrant karyotypes at first evaluation that were found in 5 of 64 (7.8%) patients rated with myelodysplasia by flow cytometry. The remaining 133 patients without proof of myelodysplasia by cytomorphology and with normal karyotype underwent follow-up analyses that confirmed myelodysplasia by cytomorphology, cytogenetics or molecular genetics in 47 (35.3%) after a median interval of nine months (range 1-53 months). As far as initial flow cytometry results are concerned, this applied to 30 of 59 (50.1%) with myelodysplasia, 10 of 42 (23.8%) with “possible myelodysplasia” (minor antigen aberrancies only) and 7 of 32 (21.9%) without myelodysplasia (P=0.004). Notably, in these latter 7 patients, flow cytometry results changed at follow up to “possible myelodysplasia” (n=4) and “myelodysplasia” (n=2). These data argue in favor of including flow cytometry along with cytomorphology, cytogenetics and molecular genetics to diagnose myelodysplasia, and suggest a closer monitoring of patients with myelodysplasia-typical aberrant antigen expression found by flow cytometry.